The properties and kinematics of HCN emission across the closest starburst galaxy NGC 253 observed with ALMA - Bešlić, Ivana; Barnes, A. T.; Bigiel, F.; Jiménez-Donaire, M. J.; Usero, A.; Henshaw, J. D.; Faesi, C.; Leroy, A. K.; Rosolowsky, E.; Brok, J. S. den; Chevance, Mélanie; Eibensteiner, C.; et al. (Astronomy and astrophysics, 2024)
Context. Investigating molecular gas tracers, such as hydrogen cyanide (HCN), to probe higher densities than CO emission across nearby galaxies remains challenging. This is due to the large observing times required to detect HCN at a high sensitivity and spatial resolution. Although approximate kiloparsec scales of HCN maps are available for tens of galaxies, higher-resolution maps still need to be available.Aims. We aim to study the properties of molecular gas, the contrast in intensity between two tracers that probe different density regimes (the HCN(1-0)/CO(2-1) ratio), and their kinematics across NGC 253, one of the closest starburst galaxies. With its advanced capabilities, the Atacama Large Millimeter/submillimeter Array (ALMA) can map these features at a high resolution across a large field of view and uncover the nature of such dense gas in extragalactic systems. Methods. We present new ALMA Atacama Compact Array and Total Power (ACA+TP) observations of the HCN emission across NGC 253. The observations cover the inner 8.6′ of the galaxy disk at a spatial resolution of 300 pc. Our study examines the distribution and kinematics of the HCN-traced gas and its relationship with the bulk molecular gas traced by CO(2-1). We analyze the integrated intensity and mean velocity of HCN and CO along each line of sight. We also used the SCOUSE software to perform spectral decomposition, which considers each velocity component separately. Results. We find that the denser molecular gas traced by HCN piles up in a ring-like structure at a radius of 2 kpc. The HCN emission is enhanced by two orders of magnitude in the central 2 kpc regions, beyond which its intensity decreases with increasing galactocentric distance. The number of components in the HCN spectra shows a robust environmental dependence, with multiple velocity features across the center and bar. The HCN spectra exhibit multiple velocity features across the center and bar, which shows a robust environmental dependence. We have identified an increase in the HCN/CO ratio in these regions, corresponding to a velocity component likely associated with a molecular outflow. We have also discovered that the ratio between the total infrared luminosity and dense gas mass, which is an indicator of the star formation efficiency of dense gas, is anticorrelated with the molecular gas surface density up to approximately 200 M⊙ pc −2. However, beyond this point, the ratio starts to increase. Conclusions. We argue that using information about spectroscopic features of molecular emission is an important aspect of understanding molecular properties in galaxies.
Gesehen am 04.06.2025